Moving Toward Findable, Accessible, Interoperable, Reusable Practices in Epidemiologic Research. - García-Closas, Montserrat; Ahearn, Thomas U; Gaudet, Mia M; Hurson, Amber N; Balasubramanian, Jeya Balaji; Choudhury, Parichoy Pal; Gerlanc, Nicole M; Patel, Bhaumik; Russ, Daniel; Abubakar, Mustapha; Freedman, Neal D; Wong, Wendy S W; et al. (American Journal of Epidemiology, 2023)
Data sharing is essential for reproducibility of epidemiologic research, replication of findings, pooled analyses in consortia efforts, and maximizing study value to address multiple research questions. However, barriers related to confidentiality, costs, and incentives often limit the extent and speed of data sharing. Epidemiological practices that follow Findable, Accessible, Interoperable, Reusable (FAIR) principles can address these barriers by making data resources findable with the necessary metadata, accessible to authorized users, and interoperable with other data, to optimize the reuse of resources with appropriate credit to its creators. We provide an overview of these principles and describe approaches for implementation in epidemiology. Increasing degrees of FAIRness can be achieved by moving data and code from on-site locations to remote, accessible ("Cloud") data servers, using machine-readable and nonproprietary files, and developing open-source code. Adoption of these practices will improve daily work and collaborative analyses and facilitate compliance with data sharing policies from funders and scientific journals. Achieving a high degree of FAIRness will require funding, training, organizational support, recognition, and incentives for sharing research resources, both data and code. However, these costs are outweighed by the benefits of making research more reproducible, impactful, and equitable by facilitating the reuse of precious research resources by the scientific community.